Absorção, translocação e efeitos metabólicos do glyphosate em plantas de eucalipto - De Castro, Edicarlos Batista [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP]; Belapart, Diego [UNESP]; Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Ben, Ronei [UNESP] (My University, 2016)
The aim of this study was to evaluate the absorption and the translocation of glyphosate applied in different positions at eucalyptus plants (Eucalyptus urograndis clone). Two experiments were conducted in a greenhouse on a completely randomized design with four replications. In the first experiment, a 3 × 2 factorial arrangement was adopted, where the factor A corresponded to the application spot on the plant (application on top, bottom and control without application) and factor B to the collection spot on the plant (top and lower). The second test was 2 × 2 factorial, where factor A corresponded to the application spot on the plant with a protected branch (branch protected on top and bottom) and factor B to the collection spot on the plant (top and bottom). The seedlings were planted in pots containing 5 liters of soil. 50 days after planting, glyphosate (360 g e.a. ha-1) was applied on both experiments and gathering occurred 4 days after application (DAA). Glyphosate, amino-methyl-phophonic acid (AMPA) and shikimic acid were quantified by liquid chromatography and mass spectrometry (LC-MS/MS). At 7, 14 and 21 DAA. The evaluation of intoxication and, at the end of the experiment, the dry mass of the plants was measured. AMPA levels were not detected in leaves. The highest percentage of absorption was observed in the application on the top of the plant. The shikimic acid levels on the applied plants were higher than those found on the controls. The application of glyphosate to the top of plant caused higher levels of poisoning and regardless which spot received the application, there was a reduction of the dry mass of eucalyptus plants. Therefore, glyphosate, after being absorbed, has mobility in eucalyptus plants, but the absence of the detection of AMPA shows that glyphosate was not metabolized in the plant.
Absorption, translocation and metabolic effects of glyphosate by Eucalyptus plants
Keywords: Eucalyptus urograndis; Intoxication; Shikimic acid